2015
DOI: 10.1088/0741-3335/57/11/115011
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Maxwellian electron energy distribution function in the vicinity of the last closed flux surface in fusion plasma

Abstract: The first-derivative probe technique was applied to derive data for plasma parameters from the IV Langmuir probe characteristics measured in the plasma boundary region in the COMPASS tokamak and in the TJ-II stellarator. It is shown that in the COMPASS tokamak in the vicinity of the Last Closed Flux Surface (LCFS) the Electron Energy Distribution Function (EEDF) is bi-Maxwellian with the low-temperature electron fraction predominating over the higher temperature one, whereas in the far scrape off layer (SOL) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 49 publications
8
33
0
1
Order By: Relevance
“…[ 16–19 ] Likewise, many laboratory experiments on Tokamaks indicated the non‐Maxwellian behaviour of electrons. [ 20–22 ] It has been found that electrons are distributed in space plasmas with modified shapes both at low and high energies. Qureshi et al, [ 12 ] therefore, devised a new non‐Maxwellian distribution function, namely, generalized (r,q) distribution function comprising two spectral indices r and q to construct the electron distribution function in agreement with the observations in the terrestrial magnetosheath.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16–19 ] Likewise, many laboratory experiments on Tokamaks indicated the non‐Maxwellian behaviour of electrons. [ 20–22 ] It has been found that electrons are distributed in space plasmas with modified shapes both at low and high energies. Qureshi et al, [ 12 ] therefore, devised a new non‐Maxwellian distribution function, namely, generalized (r,q) distribution function comprising two spectral indices r and q to construct the electron distribution function in agreement with the observations in the terrestrial magnetosheath.…”
Section: Introductionmentioning
confidence: 99%
“…Electric probes are among the most reliable diagnostic tools among the contact methods used to measure plasma parameters with sufficiently high temporal and spatial resolution in various devices [10 -16], including tokamaks and stellarators [17,18]. Sometimes, when the electron energy distribution function (EEDF) consists of a bi-Maxwellian with well-separated temperatures [17 -19], the two temperatures can be obtained by straightline fits on the semi-logarithmic discharge-voltage characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Later presence of bi-Maxwellian distribution was observed in COMPASS Tokamak and TJ-2 stellarator by using the first-derivative technique. [22] Experimental evidences of presence of hot electrons in Tokamak plasma has helped in better understanding of various phenomena. Gunn et al modified the theory of Mach probe by including bi-Maxwellian electron distribution which influenced the measured Mach number and ion sound speed.…”
Section: Introductionmentioning
confidence: 99%